Refraction of heat flow on subsurface contrast structures – the influence both on geothermal measurements and interpretation approaches - MAJCIN, Dušan; BILČÍK, Dušan; HVOŽDARA, Milan (Contributions to Geophysics and Geodesy, 2012)
The paper deals with some problems of the heat flow refractions on the subsurface structures with contrasting thermal conductivities. The qualitative and quantitative analyses of these effects were made on the selected structure configurations. Analysed structures are important particularly for the study of temperature as well as heat flow density distributions influencing the Earth’s heat flow measurements, the construction of terrestrial heat flow distribution maps and also for the interpretation of the heat flow density data. The related 2D and 3D mathematical problems were solved by means of the finite difference methods. The presented results have a great importance both for the solution of some problems of the applied geothermics (e.g. determination of the heat flow density values from measured data, their accuracy, eventual data corrections and relation of measured data to the surface heat flow density distributions) and also for the modelling of the thermal state of the lithosphere (e.g. determination of the boundary conditions and of the model check parameters, robustness of the modelling approaches, etc.).